Silenced voices: the disappearance of the university and the student teacher in teacher education policy discourse in England. Issue 2 (4th March 2019) - McIntyre, Joanna; Youens, Bernadette; Stevenson, Howard
Abstract: The teacher preparation landscape in England has been subject to radical policy change. Since 2010, the policy agenda has repositioned initial teacher preparation as a craft best learnt through observation and imitation of teachers in school settings. Simultaneously, a market-based approach to the recruitment of pre-service teachers has led to significant changes for prospective entrants to the profession. In the enactment of policy between 2010 and 2015, the roles of universities and voices of prospective teachers were systematically silenced. Using critical discourse analysis, we demonstrate how both actors have been positioned in, and have accommodated and resisted, the current policy discourses. These findings highlight the importance of problematising and understanding these emerging issues at local and international levels.